Critical Thinking and Problem Solving Skills: English for Science Foundation Program Students’ Perspectives - Tuzlukova, Victoria; Usha Prabhukanth, Katherine (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Increasing demands of the contemporary labor market environment are having a direct bearing on the courses offered by higher education institutions worldwide, and Sultanate of Oman is not an exception. One of such responses verbalized by many educational policy makers and curriculum developers in the country is an expected high level of critical thinking and problem solving skills from the students who take ESP foundation program courses. This paper reports on a study that examines to what extent ESP foundation program courses at Sultan Qaboos University in Oman impart critical thinking and problem solving skills intended for empowering our students and developing their personalities. Broadly speaking, it aims to present a comprehensive view about how critical thinking and problem solving skills teaching and learning approaches, models and practices are adopted in the context of the ESP foundation programs in Oman. More specifically, using the example of English for Science foundation program courses, it focuses on a variety of issues and context-specific factors related to ESP and critical thinking skills teaching, learning and outcomes.
Keywords: ESP; critical thinking; problem solving; foundation program; Sultanate of Oman